Fecal prevalence of Campylobacter spp. in house dogs in Lebanon: A pilot study - Ghassan Ghssein; Rana Barakat; Nada Nehme; Rana Awada; Hussein F. Hassan (Veterinary World, 2023)
Background and Aim: Campylobacter spp. are Gram-negative bacilli that are widely recognized as a primary cause of bacterial gastroenteritis worldwide. Campylobacteriosis is the disease caused by this pathogen. Recently, greater attention has been given to the prevalence of campylobacteriosis in different animals, including pets. These animals are considered to be significant reservoirs for this zoonosis. In Lebanon, the occurrence of Campylobacter infection is high. Our first-of-its-kind pilot study in Lebanon aimed to estimate the fecal prevalence of Campylobacter species in house dogs.